2020
DOI: 10.1002/smll.201906028
|View full text |Cite
|
Sign up to set email alerts
|

Virus‐Inspired Deformable Mesoporous Nanocomposites for High Efficiency Drug Delivery

Abstract: Mesoporous nanoparticles as a versatile platform for cancer theranostics have been widely used, but their cellular delivery efficiency is still far from satisfactory. Although deformability is emerging as an important parameter influencing cellular uptake enhancement, the facile synthesis of deformable mesoporous nanocomposite with adjustable mechanical property is challenging but meaningful for a deeper understanding of cellular uptake mechanisms and significantly improving cancer therapy. In this work, yolk–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Such assumptions hold true for certain inorganic NPs, such as those composed of metals and oxides . Additionally, systematic studies of silica nanocapsules with different mechanical properties have found a strong dependence of phagocytosis and tumor targeting processes , on nanoparticle stiffness.…”
mentioning
confidence: 99%
“…Such assumptions hold true for certain inorganic NPs, such as those composed of metals and oxides . Additionally, systematic studies of silica nanocapsules with different mechanical properties have found a strong dependence of phagocytosis and tumor targeting processes , on nanoparticle stiffness.…”
mentioning
confidence: 99%
“…Mesoporous nanomaterials with large surface areas, tunable pore sizes, and diverse compositions have drawn tremendous interest due to their great potential in various applications, including drug delivery, catalysis, energy conversion and storage, as well as separation technique 1 6 . In the past two decades, numerous silica-based mesoporous structures with tunable pore sizes and morphologies were constructed by a modified stöber process 7 13 , but the inert properties of silica seriously limited their applications. Therefore, metallic and semimetallic mesoporous frameworks are expected to show superior performance than silica-based mesoporous structures in electronics, catalysis, optics, and biophotonics, owing to the extraordinary electronic properties of metals and semimetals 14 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The soft particles with Young’s modulus less than 1.6 MPa were found to accumulate more in tumor tissues, while most of their stiffer counterparts (Young’s modulus > 13.8 MPa) stayed in the liver . Recently, the more deformable yolk–shell mesoporous organosilicas with lower Young’s modulus of 2.4 MPa were shown to facilitate their uptake by human breast cancer cells …”
Section: Introductionmentioning
confidence: 99%